2003
DOI: 10.2209/tdcpublication.44.201
|View full text |Cite
|
Sign up to set email alerts
|

Oral Habits of Temporomandibular Disorder Patients With Malocclusion

Abstract: The purpose of this study was to clarify the relationship between oral habits and symptoms of temporomandibular joint disorder in patients who had sought orthodontic treatment by analyzing their present and past history.The subjects were 57 female patients (average age: 23 years and 6 months old) who had visited the "Temporomandibular Disorder Section" in our orthodontic department. Their chief complaints were the symptom of TMJ and the abnormalities of occlusion such as maxillary protrusion, open bite, crowdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 6 publications
2
14
1
2
Order By: Relevance
“…15,18,31,32,41 The significant presence of diurnal and nocturnal clenching and teeth grinding (nocturnal) in this study, but not other habits, suggests the importance of bruxism on the progression and/or on non-remission of the disorder, being the clenching a more important risk factor than grinding. 6,15,30,31,40,41 And while Choi and Choung Moon 6 have reported that bruxism cannot be a direct risk factor for TMD, there are reports showing that clenching was more often associated with TMJ symptoms and clinically relevant to the occurrence of the same, increasing the risk of manifestation of TMJ pain and noise and losses in the mouth opening. 17,22,24,29,44 Therefore, a likely association between bruxism and TMD signs/symptoms supports the theory that repetitive loads on the masticatory system can cause functional disorders.…”
Section: Habitsmentioning
confidence: 55%
See 2 more Smart Citations
“…15,18,31,32,41 The significant presence of diurnal and nocturnal clenching and teeth grinding (nocturnal) in this study, but not other habits, suggests the importance of bruxism on the progression and/or on non-remission of the disorder, being the clenching a more important risk factor than grinding. 6,15,30,31,40,41 And while Choi and Choung Moon 6 have reported that bruxism cannot be a direct risk factor for TMD, there are reports showing that clenching was more often associated with TMJ symptoms and clinically relevant to the occurrence of the same, increasing the risk of manifestation of TMJ pain and noise and losses in the mouth opening. 17,22,24,29,44 Therefore, a likely association between bruxism and TMD signs/symptoms supports the theory that repetitive loads on the masticatory system can cause functional disorders.…”
Section: Habitsmentioning
confidence: 55%
“…1,27,33 The significant correlation between the frequency and severity of signs and symptoms are an indication that the larger the number of signs and symptoms, the greater the severity perceived by the patient. And, although several authors suggest that the habits accumulation can lead to worsening or contribute to no remission of the present scenario, and deleterious oral habits are among the TMD etiological factors, 15,19,30,31,32 the frequency of habits was not correlated to the frequency or severity of signs and symptoms, according to data analyzed from ProDTMMulti 13 in the current population. In a previous study, it was suggested that, in relation to bruxism, there is an effect of habit in time 30 .…”
Section: Habitsmentioning
confidence: 62%
See 1 more Smart Citation
“…Offenbar laufen bei der Eingliederung kieferorthopä-discher Apparaturen ähnliche Muster wie bei der Eingliederung von "Knirscherschienen" ab [29]. Zwar haben Fujita et al [14] bei ihren kieferorthopädischen Patienten keine Verän-derungen von Bruxismusaktivitäten während der Dauer der Behandlung festgestellt, allerdings ist die statistische Power dieser Aussage bei einer Probandenzahl von 57 auch nicht sehr hoch. Es scheint plausibel, dass die temporäre Unterbrechung parafunktioneller Aktivitäten während der kieferorthopädischen Behandlung langfristig als positiver Begleitbefund in Erscheinung tritt.…”
Section: Discussionunclassified
“…Apparently when orthodontic appliances are inserted a similar pattern arises as when occlusal devices are worn [29]. Although Fujita et al [14] reported no changes in bruxing behavior in their orthodontic patients during their treatment period, their claim's statistical significance is rather minimal as they had only 57 probands. It seems reasonable to assume that the temporary interruption of parafunctional activities during orthodontic treatment is a positive secondary feature over the long term.…”
Section: Diskussionmentioning
confidence: 99%